Linguistic theory and ’communicattve’ modern language, teaching: the future shows change - New, James W. (Lenguas Modernas, 2017)
According to one of its foremost proponents the influence of transformational generative linguistics (TGG) is waning. This waning influence can be noticed largely in disciplines related to linguistics such as psychology but not among many professional linguistis and language teachers. If this is so, two questions might be asked before a look into the future can be attempted: (1) Wha was transformational grammar? And (2) How dtd it affect language teaching in general and TESL in particular? These two questions are related to two other questions. 1) What was the extent of the inlluence of TCG on language teaching? and (2) How long will this influence remain? The answers to these two questions are largely speculative but are nevertheless interesting and hence are the focus of this report.